Penggunaan Dinamometer Tangan Sebagai Instrumen Asesmen Klinis - Ilhamy, Satria Rizqi; Setiorini, Anggi; Ratna, Maya Ganda; Ismunandar, Helmi (CV. Jasa Sukses Abadi, 2024)
Hand is one of the system organs in the human bodies consisting of bones, muscles, and nerves that works in unison in order to function well. Hand plays a crucial role in daily activities hence it needs to have a good function. One of the main method to assess one’s hand function is by their handgrip strength measured by a hand dynamometer. Hand grip strength measured by a hand dynamometer can be used as a certain health indicator in clinical settings either as a diagnostic tool or as a prognostic predictor for some diseases. One of the use of hand grip strength measured by a hand dynamometer is to diagnose sarcopenia, a musculoskeletal degenerative disease that affects the elderly because of their aging process. Research showed a relationship between a low results of hand grip measurement with an increase of the risk of death in pneumonia patients caused by COVID-19. The results from the dynamometer can also be used as a predictor of success for weaning off a ventilator. Other research also found a correlation between the hand grip measurement with the degree of severity in type 3 spinocerebellar ataxia. Hand grip measurement is relevant for assessing clinical outcomes in patients with incurable cancer. Another study found that hand grip strength measurement can be used to assess chronic kidney disease patient’s vascular diameter for their vascular access in order to continue their hemodialysis. Therefore, dynamometer has a potential as a clinical assessment instrument to support diagnostic and prognostic accuracy.